1995
DOI: 10.1007/bf01716281
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of detectability of hepatitis C virus genome in saliva of elderly Japanese symptomatic HCV carriers with their hepatic function

Abstract: The hepatitis C virus (HCV) genome was sought in the saliva of 76 chronic HCV carriers (mean age nearly 60 years) in a rural Japanese town, who had high serum titers of c-100 and anti-core second generation antibodies. In 27 samples (27 cases, 36%), the HCV-RNA genome was detected by the reverse transcriptase - polymerase chain reaction with either of two sets of primers covering two regions of the HCV genome: the 5'noncoding region and the region encompassing the putative envelope (E1). Transaminase values at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…IVDU, intravenous drug users. d Schneeberger et al, 1998. [ Tai-Cheng Liou et al, 1992;Sugimura et al, 1995;Roy et al, 1998Roy et al, , 1999Fabris et al, 1999]. Several explanations might be given.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…IVDU, intravenous drug users. d Schneeberger et al, 1998. [ Tai-Cheng Liou et al, 1992;Sugimura et al, 1995;Roy et al, 1998Roy et al, , 1999Fabris et al, 1999]. Several explanations might be given.…”
Section: Discussionmentioning
confidence: 89%
“…First, the clinical status of the participants in the various studies might have in¯u-ence on the results. The study population described by others consisted of subjects who had been diagnosed with chronic hepatitis [Fabris et al, 1999;Roy et al, 1999;Sugimura et al, 1995]. In the present study, liver function tests were not carried out.…”
Section: Discussionmentioning
confidence: 97%
“…However, some authors have reported that they were able to detect HCV in saliva samples from patients, but could not detect HCV in their blood [6,8,12,14,25]. A possible explanation for such findings is the fact that HCV can replicate in oral epithelial cells in patients without HCV in the blood, as demonstrated by Arrieta et al [49] in HCV positive patients with and without oral lichen planus.…”
Section: Discussionmentioning
confidence: 99%
“…Five out of 38 publications reported100% HCV-RNA detection in saliva samples from HCV-positive patients [16,17,25,29,38]; however, only a few cases or only patients with sialoadenitis were considered in these studies, which may represent a caveat. When reports with sample sizes larger than 30 HCV-positive patients were considered separately, the broad variability of frequencies was evident, ranging from 0 to 66% [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This variation in HCV-RNA detection frequencies in saliva samples may be due to the saliva sampling method used.…”
mentioning
confidence: 99%
“…HCV infection may account for the pathogenesis of a subgroup of Sjögren syndrome, which is considered to be a multifactorial disease (33,34). Although the HCV genes were expressed under the control of an exogenous promoter in these transgenic mice, the presence of HCV in human saliva has been reported either through the detection of HCV in human saliva or transmission of hepatitis via saliva (37)(38)(39) sialadenitis and suggest a direct role of the viral protein(s) in the pathogenesis of sialadenitis that develops in chronic HCV infection. This mouse system might be a good animal model for studying the pathogenesis of sialadenitis and other HCVassociated extrahepatic manifestations.…”
Section: Discussionmentioning
confidence: 99%